Pendampingan Pemasaran Produk Makanan Ringan Berbahan Buah Salak pada UMKM Geplak Salak di Dusun Jengglik - Muhamad Safiqul Umam; Yeny Fitriyani; Achmad Nur Alfiyanto (Warta Pengabdian Andalas, 2023)
Micro, small and medium enterprises (MSMEs) are essential for economic growth, especially in rural areas. However, many MSMEs need help marketing their products, including Geplak Salak MSMEs in Jengglik Village. Mentoring aims to assist in marketing by utilizing social media and product labels to increase market reach and product selling value. The assistance was carried out in March-April 2022. The target of the assistance was MSMEs that produce food using snake-fruit as the primary ingredient, which was processed into ready-to-eat food, namely Geplak Salak. This assistance used an asset-based community development (ABCD) approach to improve marketing strategies through training in social media. The result of this training was the creation of a product logo that suits the preferences of MSME owners and increased product exposure on the Instagram and Facebook platforms, which can help expand the product's market reach. In conclusion, promoting social media can be an effective solution to overcome the marketing challenges MSMEs face.